“É de verdade ou é de plástico?”: formas e sentidos das críticas ao forró eletrônico - Silva, Cícera Tayane Soares da (2016)
This dissertation discusses the criticisms made to the electronic forró involving musicians, culture secretaries, professors, event producers and lovers of electronic forró. From the postulates of such authorities, the dissertation aims to understand forms and meanings of criticism to electronic forró, understanding their senses and meanings. More than pointing distinctions, we aims to understand in what pillars such critics are grounded to. For this, we use the three most frequent criticism observed: the origin, the objectification of women and commodification. From these questions, we will see how the taste issue constitutes an important prerogative for such positions are realized. Thus, we attempt to understand how and why these criticisms are often used to delegitimize the electronic forró and its cultural significance. From this script, we noted how these spaces and critical phenomenon of observation (origin, women's objectification and commodification) converge to produce a speech from agents and specific sectors of society on electronic forró in a context of struggle for meaning and representation.